Spirit christology - Dahlke, Benjamin (Edinost in dialog, 2024)
Spirit Christology has resonated within Anglican, Protestant, and Catholic theology. This is due to several limits of the traditional approach based on the formula of Chalcedon which have been highlighted since the 18th century. Entangling Christology and Pneumatology is regarded a promising solution to the notorious problem of explaining the person of Jesus Christ. In this paper, both the intentions and the challenges of Spirit Christology are being displayed. An important aspect will be to differentiate between two types of Spirit Christology: first, attempts to deepen and enrich the understanding of the traditional approach, and second, attempts to replace it. In recent theological discourse, both views are being expressed.
Keywords: christology; council of Chalcedon; kalcedonski koncil; kristologija; kristologija Duha; pneumatology; pnevmatologija; Spirit-christology